2016
DOI: 10.15252/embr.201642360
|View full text |Cite|
|
Sign up to set email alerts
|

Glioma‐derived cancer stem cells are hypersensitive to proteasomal inhibition

Abstract: Although proteasome inhibitors (PIs) are used as anticancer drugs to treat various cancers, their relative therapeutic efficacy on stem cells vs. bulk cancers remains unknown. Here, we show that stem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Glioma, a kind of malignancy arising from glial cells in the brain, is the most common malignant tumours occurring in the central nervous system and accounting for 78% of intracranial primary tumours 1, 2. Glioma usually exhibits a series of malignant features, including extensive, rapid and aggressive progression, resistance to surgery, radiotherapy and chemotherapy, all of which lead to the poor prognosis for most patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma, a kind of malignancy arising from glial cells in the brain, is the most common malignant tumours occurring in the central nervous system and accounting for 78% of intracranial primary tumours 1, 2. Glioma usually exhibits a series of malignant features, including extensive, rapid and aggressive progression, resistance to surgery, radiotherapy and chemotherapy, all of which lead to the poor prognosis for most patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted here that the therapeutic arsenal of oncologists also includes hyperthermia and inhibitors of proteasomes (e.g., bortezomib); CSCs were shown to be very sensitive to either of these exposures [172,173] and co-treatments with hyperthermia or proteasome inhibitors are suggested for sensitizing CSCs to chemotherapy and radiotherapy. The sensitizing effects appear to be due to the accumulation of misfolded proteins in heated or proteasome inhibitor-treated CSCs because these excess misfolded proteins recruit cytosolic chaperones, which thus become unable to maintain the chaperone-dependent features of CSCs, such as chemoresistance and radioresistance.…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…Multiple studies have confirmed the existence of CSCs in glioma, or glioma stem cells (GSCs), which are capable of self-renewal, extensive proliferation, and multi-lineage differentiation [ 9 , 14 , 19 ]. These studies have demonstrated that the rare population of GSCs is necessary and sufficient to initiate, maintain, and recapitulate the phenotype of original glioma in immune-compromised mice, and when GSCs are eliminated from the bulk tumor mass, tumor growth is inhibited [ 36 , 37 ]. Therefore, GSCs could play a pivotal role in glioma development in human, and these cells seem to be a promising target for glioma therapies [ 38 ].…”
Section: Introductionmentioning
confidence: 99%